Gambaran Status OHI-S dan Pengetahuan Menyikat Gigi di POLRES Batalyon B Pelopor Kota Baubau Sulawesi Tenggara - Asriawal; Angki, Johnny; Fita Dwiasrianti, Wa Ode (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Maintaining oral and dental hygiene is an essential part of preserving overall health and preventing various diseases. To achieve optimal health, oral and dental hygiene must be properly cared for. One method to evaluate oral cleanliness is by assessing the oral hygiene status using the OHI-S (Oral Hygiene Index-Simplified). This study aims to determine the OHI-S status at Battalion B Pioneer Police Unit, BauBau City, Southeast Sulawesi. The research method applied was observational, involving direct oral examinations and the distribution of questionnaires. The study was conducted at Battalion B Pioneer Police Unit in BauBau City, Southeast Sulawesi. The results showed that the average OHI-S status of respondents fell into the moderate category, while knowledge levels about proper toothbrushing were categorized as good. Based on statistical analysis using the chi-square test, a significant relationship was found between OHI-S status and knowledge levels. Conclusion: There is a significant correlation between OHI-S status and the level of knowledge about toothbrushing.